(untitled) (Letters in Nonlinear Analysis and its Applications, 2024)
Numerous researchers worldwide have reported on the search for reliable methods to relate heat transfer to stagnation point flows. This paper studies the Hiemenz flow of a recently evolved hybrid nanofluid over a porous surface. To achieve the desired surface properties, kerosene oil is infused with nanoparticles of aluminum oxide and copper. Further, heat transfer due to isothermal radiation flux and dissipation by vicious means is examined. Supervising boundary value problems (BVPs) consist of partial differential equations (PDEs) which are transformed into ordinary differential equations (ODEs) through suitable similarity transformations. Infinite series solutions are obtained by the semi-analytic Homotopy analysis method (HAM), whereas numerical estimations are also conducted using the \(bvp4c\) collocation code. The software used to obtain the above solutions is MATHEMATICA and MATLAB, respectively. A graphical and tabular representation of the effects of parameter variations on dimensionless velocity, temperature, skin friction coefficient, and Nusselt number is included. It is found that the radiation parameter enhances convection. Moreover, the injection significantly improves surface drag measures of kerosene-based hybrid nano-oil, while suction at the surface positively affects heat transfer and improves it. Despite that, the rise in the porosity factor diminishes the drag coefficient range.